2018
DOI: 10.1021/acs.chemmater.8b02926
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Silica Nanotube Aerogels Inspired by Polar Bear Hair for Light Management and Thermal Insulation

Abstract: Designing macroscopic, 3D porous multifunctional materials is of great importance in many fields, including energy storage, thermal insulation, sensors, and catalysis. Polar bears have hairs with a membrane-pore structure, which contributes to adaptation to harsh environments. Inspired by polar bear hair, this study reports a facile route to fabricate multifunctional silica nanotube aerogels (SNTAs) via chemical vapor deposition (CVD) of silica onto the sacrificial carbon nanoskeleton of a carbon aerogel (CA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 44 publications
0
92
0
Order By: Relevance
“…Ceramic aerogels based on SiO 2 , [ 74 ] Al 2 O 3 , [ 75 ] SiC, [ 76 ] and BN [ 77 ] have been widely investigated due to their light weight, low thermal conductivity, high refractoriness, and corrosion resistance. As a well‐known example, thermal insulation systems of extraordinarily high performance have been achieved on the basis of silica aerogels and emerging as the first significantly commercialized aerogel materials.…”
Section: Recent Trends In Freeze‐casting Materialsmentioning
confidence: 99%
“…Ceramic aerogels based on SiO 2 , [ 74 ] Al 2 O 3 , [ 75 ] SiC, [ 76 ] and BN [ 77 ] have been widely investigated due to their light weight, low thermal conductivity, high refractoriness, and corrosion resistance. As a well‐known example, thermal insulation systems of extraordinarily high performance have been achieved on the basis of silica aerogels and emerging as the first significantly commercialized aerogel materials.…”
Section: Recent Trends In Freeze‐casting Materialsmentioning
confidence: 99%
“…Kistler first presented the composition of aerogels including oxides of silicon, aluminum, tin, thorium, iron, tungsten and organic compounds such as cellulose, cellulose nitrate, and gelatin [5,6]. For a long time, as a representative of inorganic aerogels, silica aerogels have been widely studied and applied because of their low cost and good structure and properties [7,8]. In the field of biomedicine, previous studies have shown the diffusion mechanism of drugs in silica aerogels [9,10], and that silica nanoparticle-loaded drugs have had good targeted therapeutic effects on diseases [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Through evolution over millions of years, elaborate biophotonic microstructures existing in creatures have been fascinating tools to efficiently control the light propagation, leading to tremendous advances in design of modern biomimetic materials and devices . Structural whiteness (i.e., broadband reflection) is one of the intriguing phenomena, which prevalently appears in insects, aquatic organisms, mammals, and avifaunae, providing ponderable ideas for applications ranging from displays to energy‐efficient thermal controlled materials and devices . Derived from the correlation between intensity of reflection light and viewing or incident angles, structural whiteness can be divided into two types, diffuse whiteness (angle independent) and metallic silver (angle dependent).…”
Section: Introductionmentioning
confidence: 99%